Easy and Green Route towards Nanostructured ZnO as an Active Sensing Material with Unexpected H2S Dosimeter‐Type Behaviour. Issue 6 (30th January 2019) - Diodati, Stefano; Hennemann, Jörg; Fresno, Fernando; Gialanella, Stefano; Dolcet, Paolo; Lavrenčič Štangar, Urška; Smarsly, Bernd M.; Gross, Silvia
Abstract : Nanostructured ZnO particles were prepared through a straightforward, quick and low‐temperature synthesis route involving coprecipitation of the metal precursor salts with oxalic acid, followed by hydrothermal treatment at 135 or 160 °C. The synthesised nanostructured powders were thoroughly characterised by a wide array of analytical techniques from the morphological (Scanning Electron Microscopy ‐SEM‐, Transmission Electron Microscopy ‐TEM‐, Energy‐dispersive X‐ray Spectroscopy ‐EDXS‐), structural (Powder X‐ray Diffraction ‐PXRD‐, Selected Area Electron Diffraction ‐SAED‐), compositional (X‐ray Photoelectron Spectroscopy ‐XPS‐) and physical (thermal stability) point of view. As far as functional applications are concerned, the powders were tested as gas sensor materials for H2 S detection. Thereby these ZnO particles showed unexpected gas dosimeter behaviour at 150 °C. Based on these observations and on a comparison with literature a new model for the interaction of ZnO nanostructures with H2 S is proposed. Abstract : Nanostructured ZnO was synthesised through a quick, easy, low‐temperature and green hydrothermal route, showing an interesting gas‐sensing behaviour. At an operation temperature of 450 °C, the material exhibits a significant response to H2 S gas exposure as expected for a semiconducting n‐type gas sensor. However, at an operating temperature of 150 °C the material shows gas dosimeter‐type behaviour.